Preliminary geophysical study for groundwater exploration in the eastern region of Islamabad - Khan, K. A. (Journal of Nepal Geological Society, 1996)
Geophysical study was carried out in the area lying to the east of Islamabad to identify potential aquifers and to establish the relationship between the geoelectric and hydrogeologic parameters. Electrical resistivity survey using the Schlumberger electrode configuration was carried out at 32 stations. Data processing and interpretation were done using a PC based software. The true resistivity and thickness of various subsurface horizons were interpreted in terms of geological columns and cross-sections to reveal the presence of clay, sand, gravel and boulders as the subsurface lithology. The wide occurrence of gravels and boulders suggest that most of the regions in the project area represent the promising zone of groundwater. Both confined and unconfined aquifers have been encountered. The resistivity information was used to plot Dar-Zarrouk curves across selected profiles in order to determine the electrical behaviour of the aquifer. These curves show that the surficial layer is composed of material of high resistivity while the second layer constitutes the aquifer having high longitudinal conductance. Finally, statistical analyses involving linear regression were carried out to find out the relationship between electric and hydraulic properties of the aquifers. The results indicate that there is no significant relationship between the two parameters. All the results were compiled to demarcate promising groundwater drill sites.